Tenascin-C induction exacerbates post-stroke brain damage. Issue 2 (February 2022) - Chelluboina, Bharath; Chokkalla, Anil K; Mehta, Suresh L; Morris-Blanco, Kahlilia C; Bathula, Saivenkateshkomal; Sankar, Sneha; Park, Jin Soo; Vemuganti, Raghu
The role of tenascin-C (TNC) in ischemic stroke pathology is not known despite its prognostic association with cerebrovascular diseases. Here, we investigated the effect of TNC knockdown on post-stroke brain damage and its putative mechanism of action in adult mice of both sexes. Male and female C57BL/6 mice were subjected to transient middle cerebral artery occlusion and injected (i.v.) with either TNC siRNA or a negative (non-targeting) siRNA at 5 min after reperfusion. Motor function (beam walk and rotarod tests) was assessed between days 1 and 14 of reperfusion. Infarct volume (T2-MRI), BBB damage (T1-MRI with contrast), and inflammatory markers were measured at 3 days of reperfusion. The TNC siRNA treated cohort showed significantly curtailed post-stroke TNC protein expression, motor dysfunction, infarction, BBB damage, and inflammation compared to the sex-matched negative siRNA treated cohort. These results demonstrate that the induction of TNC during the acute period after stroke might be a mediator of post-ischemic inflammation and secondary brain damage independent of sex.